Auditory fatigue among call center operators with headset - Pretty Omar Afifi (The Egyptian Journal of Otolaryngology, 2020)
Abstract Background To assess whether call center operators are subject to or suffer from any auditory fatigue when compared to normal subjects. A prospective case-control study where twenty-eight call center operators (10 females and 18 males) with an age range from 25 to 46 years and twenty controls (12 females and 8 males) with an age range from 23 to 44 years were included. All call center operators use a headset for up to 8 h daily for a minimum of two consecutive years. Audiological assessments were done to all participants that included pure tone audiometry (PTA), speech audiometry, tympanometry, and acoustic reflexes. Moreover, transient-evoked otoacoustic emission (TEOAE) absolute threshold and distortion product otoacoustic emission (DPOAE) signal to noise thresholds as well as contralateral suppression of TEOAEs and DPOAEs were recorded for both groups. Results There was no significant variation in auditory performances detected with either PTA or OAE (TEOAEs and DPOAEs) test. Besides, there was no statistically significant difference in OAEs (TEOAEs and DPOAEs) with contralateral suppression for both the call center operators and control groups. However, call center operators expressed a feeling of tiredness. Conclusions There was no detectable central or peripheral auditory fatigue experienced by the call center operators when using headsets. However, their sensation of auditory fatigue could be due to cognitive fatigue rather than noise-induced fatigue.